GAMBARAN PROGRESIVITAS DAN PROGNOSIS PADA PASIEN CA PARU DI RSUD. DR. H. ABDUL MOELOEK PROVINSI LAMPUNG TAHUN 2018-2021 - Fransisca Tarida Yuniar Sinaga; Jordy Oktobiannbel; Retno Ariza Soeprihatinin Soemarwoto; Via Yuananda (CV. Jasa Sukses Abadi, 2022)
Lung cancer is all malignancy that occurs in the lung and originates from the lung itself (primary) and can even occur from outside the lung (metastasis). 2. Smoking is the highest risk factor for lung cancer. In general, the early stages do not cause prominent complaints, but over time general complaints can be seen. 3. Many lung cancer patients are diagnosed at stage III and IV so that the life expectancy is lower. This study aims to determine the frequency distribution of pulmonary CA patients in hospitals. DR. H. Abdul Moeloek Lampung Province in 2018-2021 with quantitative descriptive research methods. Lung cancer patients were male (73.8%) and female (26.2%) mostly aged 35-65 (70.9%), without a family history of lung cancer (77.9%), had a history of lung cancer. smoking (75.0%), found in stage IV B (37.7%), stage IV A (37.3%), stage III B (15.6%) and stage III A (15.6%). Most lung cancer patients were found without comorbid (41.8%), accompanied by complications of pleural effusion (35.2%) with contralateral lung metastases (32.8%). Most local metastases are found in the contralateral lung and distant metastases are often found in the brain. Early detection is important because the speed of treatment greatly affects the prognosis of the disease.